Enhancement of traditional mode of teaching based on the experience of Project-Based Learning - Ambikairajah, E.; Thiruvaran, T.; Eaton, R. (IEEE, 2013)
Project based learning (PBL) has become more popular due to its student centered nature of learning compared to traditional modes of learning. However, it is not always feasible to implement it due to several reasons. At the University of New South Wales, the PBL mode was trialled on an introductory Digital Signal Processing course for two consecutive years and the evaluation was previously reported. After that, based on the experience of PBL implementation, some elements of PBL have been incorporated with traditional mode of teaching to enhance the traditional mode and that enhanced traditional mode have been continued. The experience of enhancing the traditional mode with components derived from PBL, particularly the inclusion of conceptual design presentation and laboratory tests, are promising. This paper presents the task description of PBL and experience of how some of the components of PBL can be utilized to enhance the traditional mode of teaching.
Keywords: Project Based Learning; igital Signal Processing